Evaluation of prevalence, diagnostic, and surgical treatment of cancerous lesions of the ocular region in Hereford and Polled hereford cattle - Viana, José Garibaldi Leite; Fialho, Sérgio Amaro Guimarães; dos Santos, Murilo Nogueira; de Barros, Cláudio Severo Lombardo; Raiser, Alceu Gaspar; da Silva, Diógenes Odilon Santos (Pesquisa Agropecuaria Brasileira, 1992)
Twenty-nine ocular and palpebral tumoral growths were observed in a 30-month-period of clinical observation carried out in 1,700 Hereford and Polled Hereford cattle. Twenty three affected animals were submitted to surgery; of those 21 had squamous cell carcinomas and two had chronic inflammatory lesions. Surgical treatment consisted of tumor excision either with or without extirpation of the globe. Reincidences were observed in 9.5% of the cases within a 6-month-period of postsurgical observation. Six animals with tumoral growths were not treated. The prevalence of clinically diagnosed ocular carcinomas in a slaughterhouse located within the area of the study was 0.16%.